A systematic review on the Roles and Responsibilities of Sport Manager’s Professional Competency - Daniel Getnet Admit (Publikasi Indonesia, 2023)
Management is one of the most important human activities and has a critical impact on the life, growth, development, or destruction of organizations. The skills necessary for management vary at different levels, and their distinction necessitates the identification of roles and responsibilities that managers use to play. Even skills vary according to the level of management. This systematic review aims to synthesize the roles, responsibilities, and skills of sport managers. This is an attempt to use PRISMA meta-synthesis. By using keywords like